2020
DOI: 10.1155/2020/8852570
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Leaf and Rootstock Aqueous Extracts of Foeniculum vulgare on Chemical Profile and In Vitro Antioxidant and Antihyperglycemic Activities

Abstract: Foeniculum vulgare is a medicinal plant used in Moroccan folk medicine to treat several diseases such as diabetes. The aim of this study was to determine the phenolic bioactive compounds and to evaluate the antioxidant and antihyperglycemic activities of Foeniculum vulgare leaf and rootstock extracts. Phenolic compounds of F. vulgare rootstock and leaf extracts were determined using HPLC-DAD-QTOFMS analysis. The antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azinobis-(3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(44 reference statements)
2
5
0
Order By: Relevance
“…The current study showed weaker inhibitory activity of methanolic extracts of C. absus than a previous contrasting study which reported that hydroalcoholic extracts of C. absus had potent inhibitory activity against α-glucosidase ( 119 ). However, The results of the present investigation are per the majority of earlier research, which reported that C. citratus ( 115 ), M. arvensis ( 120 ), F. vulgare ( 121 ) had strong α-glucosidase inhibition activity due to their high phytochemical contents, such as alkaloids, flavonoids, and saponins that bind other non-competitive enzymes ( 119 ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The current study showed weaker inhibitory activity of methanolic extracts of C. absus than a previous contrasting study which reported that hydroalcoholic extracts of C. absus had potent inhibitory activity against α-glucosidase ( 119 ). However, The results of the present investigation are per the majority of earlier research, which reported that C. citratus ( 115 ), M. arvensis ( 120 ), F. vulgare ( 121 ) had strong α-glucosidase inhibition activity due to their high phytochemical contents, such as alkaloids, flavonoids, and saponins that bind other non-competitive enzymes ( 119 ).…”
Section: Resultssupporting
confidence: 67%
“…The main mechanisms of caffeic acid, which regulates blood glucose levels, are stimulating insulin production, triggering glucose uptake by adipocytes in the liver, and reducing the glucose level in the bloodstream. In general, phenolic compounds can alter carbohydrate metabolism by their binding affinity towards hydrolyzing enzymes ( 121 ). Present study confirms the antidiabetic activity of selected plant extracts which indicates their suitability for use in therapeutic medicine.…”
Section: Resultsmentioning
confidence: 99%
“…A. Bashkin and his colleagues found that two of the D-P have very weak α-amylase inhibition: F. vulgare and G. tournefortii [106]. This contradicts previous reports for F. vulgare [47,52,57], and even more for G. tournefortii [65], where M. Keskin and her colleagues reported very high activity of this enzyme inhibition: IC 50 = 4.22 mg/mL. And the last contradiction for F. vulgare, we find in the report of F. Amirkhanloo and her colleagues that the essential oil of this plant could not improve insulin resistance in women with polycystic ovary syndrome, PCOs [107].…”
Section: Foeniculum Vulgarementioning
confidence: 87%
“…4. [52] Seeds were extracted with 20% aqueous ethanol, and cookies that contained 3% extract were supplemented to hyperglycemic human subjects (4 cookies in a single dose, mass not indicated). Tests indicated significant reduction of blood glucose concentrations [53].…”
Section: Foeniculum Vulgarementioning
confidence: 99%
“…Until now, only a few research studies have assessed the effects of fennel products on diabetes. Most studies were performed in vitro, but preclinical studies have evaluated the effects of different extracts from fennel on diabetic rats [ 13 , 14 , 15 ]. While the in vitro studies have shown promising effects, information from in vivo studies is scarce.…”
Section: Introductionmentioning
confidence: 99%